Economic Impact of Tourist Expenditure on Tourism Industry in Penang - Chong, Yee Lee (2011)
Dubbed “The Pearl of the Orient,” Penang is a popular tourism destination in Malaysia since the colonial days. The situation has somewhat changed as it is now losing out to other destinations. The local government is aware of the economic contribution of tourism; the contribution composes of (1) direct effect – revenues generated from tourist expenditure and (2) indirect effect – creation of additional output sales and employment for the local community. However, assessing the indirect economic benefit of tourism is difficult. The collection of the following data is not a simple task for researchers: the amount of tourist expenditure that is received and then spent by tourism establishments. This thesis aims to estimate the direct and indirect effects of tourist expenditure on the tourism sector in Penang, The thesis’s findings can provide policy implication to the local government and guidance to other tourism interests for the development of tourism. Most of the published data are not suitable for the analysis of tourism’s economic impact because these data do not segregate the sales of tourism establishments by tourists and local residents. Therefore, two surveys are undertaken: (1) questionnaires are distributed to estimate the tourist respondents’ spending that accrues to the host community. (2) On top of the distribution of questionnaires to selected tourism establishments, observation method is employed to cross-check the estimation of tourist count provided by the tourism establishment respondents. Both quantitative and qualitative data are used to construct two different Input-Output (I-O) tables. I-O model is used to estimate the proportion of sale revenues of each tourism sector – including the accommodation, food, freight, shopping, entertainment, and miscellaneous sectors – that is used for the purchases of primary inputs (such as wages, dividend, profit, imports and taxes) and intermediate inputs. I-O multipliers are computed to measure the indirect effects generated by tourism establishments’ spending within the local economy. However, the total estimates of output sales and input purchases for each I-O sector are rarely equal. Jensen and McGaurr (henceforth J-M) have recommended the use of “reliability quotients” for the dual estimates. Sahal Lahiri (henceforth SL) suggests that analysts determine the reliability quotients endogenously so that the time costs can be reduced. Each quantitative and qualitative I-O table is reconciled by both the J-M and SL methods. The I-O multiplier values produced by quantitative and qualitative data are quite similar. However, the reconciliation methods produce different multiplier values for the same I-O tourism sector. This is because both techniques are using different formulae. Some of the research empirical findings fit nicely into well-known literature and can be summarized under three empirical patterns: (1) the more developed a tourism destination is, the more tourism and supplies firms will be established within the region’s economy. (2) More tourist expenditure can take place within the region’s economy if the local economic structure is diversified. (3) Though seasonality – implying seasonal increase in labour – is much less of a problem in Penang, the domination by many small scale establishments operated by family members also means that not much job opportunities can be created. Consistent with the literature, the low technical coefficient values show that the linkages between tourism sectors are weak because the supply chain practice by tourism service firms is low in nature. Expanding the tourism industry in Penang will increase the tourist expenditure within the region’s economy. Attempts should be made to broaden the area’s tourist attractions and to diversify the tourism businesses. As a result, more tourists may come and may also extend their length of stay and therefore spend more money within the local area. To reduce the dependency on imported goods, the shopping establishments need to introduce more locally produced crafts or souvenirs or agricultural products.